Obremenjenost zraka s cvetnim prahom v letu 2021 - Kofol-Seliger, Andreja (Naše okolje, 2021)
The article presents the main characteristics of the pollen season in the year 2021. The pollen measurements has been performed in the central part of the country in Ljubljana, in Izola on the Coast, in Maribor, and in Lendava.
Keywords: cvetni prah; Lendava; Ljubljana; Maribor; obremenjenost zraka